3T MR‐guided in‐bore transperineal prostate biopsy: A comparison of robotic and manual needle‐guidance templates. Issue 1 (27th September 2014) - Tilak, Gaurie; Tuncali, Kemal; Song, Sang‐Eun; Tokuda, Junichi; Olubiyi, Olutayo; Fennessy, Fiona; Fedorov, Andriy; Penzkofer, Tobias; Tempany, Clare; Hata, Nobuhiko
<x xml:space="preserve">Abstract</x> Purpose To demonstrate the utility of a robotic needle‐guidance template device as compared to a manual template for in‐bore 3T transperineal magnetic resonance imaging (MRI)‐guided prostate biopsy. Materials and Methods This two‐arm mixed retrospective‐prospective study included 99 cases of targeted transperineal prostate biopsies. The biopsy needles were aimed at suspicious foci noted on multiparametric 3T MRI using manual template (historical control) as compared with a robotic template. The following data were obtained: the accuracy of average and closest needle placement to the focus, histologic yield, percentage of cancer volume in positive core samples, complication rate, and time to complete the procedure. Results In all, 56 cases were performed using the manual template and 43 cases were performed using the robotic template. The mean accuracy of the best needle placement attempt was higher in the robotic group (2.39 mm) than the manual group (3.71 mm, P < 0.027). The mean core procedure time was shorter in the robotic (90.82 min) than the manual group (100.63 min, P < 0.030). Percentage of cancer volume in positive core samples was higher in the robotic group (P < 0.001). Cancer yields and complication rates were not statistically different between the two subgroups (P = 0.557 and P = 0.172, respectively). Conclusion The robotic needle‐guidance template helps accurate placement of biopsy needles in MRI‐guided core biopsy of prostate cancer. J. Magn. Reson. Imaging 2015;42:63–71. © 2014 Wiley Periodicals, Inc.